Long-term efficacy and toxicity of abacavir/lamivudine/nevirapine compared to the most prescribed ARV regimens before 2013 in a French Nationwide Cohort Study. Issue 37 (September 2016) - de Boissieu, Paul; Dramé, Moustapha; Raffi, François; Cabie, André; Poizot-Martin, Isabelle; Cotte, Laurent; Garraffo, Rodolphe; Delobel, Pierre; Huleux, Thomas; Rey, David; Bani-Sadr, Firouzé; ,
Abstract : Abstract: Data on the long-term efficacy and safety of abacavir/lamivudine (ABC/3TC) and nevirapine (NVP) are scarce. This combination has the advantage of simplifying treatment and improving long-term tolerance. The aim of this study was to compare the rate of any discontinuation of antiretroviral (ARV) regimen because of virologic failure (VF), and/or adverse drug reaction (ADR) among patients receiving stable ARV regimens for at least 6 months. ABC/3TC/NVP was compared to ABC/3TC with either ritonavir-boosted darunavir (DRV/r) or ritonavir-boosted atazanavir (ATV/r), unboosted ATV, or tenofovir/emtricitabine (TDF/FTC) with either one of the following: ATV/r, unboosted ATV, DRV/r, efavirenz (EFV), or NVP, in the French prospective multicenter Dat'AIDS cohort. The study enrolled 16, 511 patients treated with following ARV regimens: ABC/3TC/NVP (n = 1089), TDF/FTC/NVP (n = 1542), ABC/3TC/DRV/r (n = 1065), ABC/3TC/ATV/r (n = 1847), ABC/3TC/ATV (n = 563), TDF/FTC/ATV/r (n = 3519), TDF/FTC/DRV/r (n = 2767), TDF/FTC/ATV (n = 419), and TDF/FTC/EFV (n = 3700). Mean follow-up was 36 ± 24 months. Patients treated with ABC/3TC/NVP received this regimen as a switch regimen in 97% of cases. By multivariable analysis, the risk of treatment discontinuation due to VF was similar between ABC/3TC/NVP and other ARV regimens, except for TDF/FTC/ATV and ABC/3TC/ATV, which were associated with a higher risk of treatment interruption due to VF (hazard ratio [HR] 1.99; 95% confidence interval [CI] 1.29–3.06 and HR 2.19; 95% CI 1.51–3.18, respectively). Treatment discontinuation due to ADR was lowest with the ABC/3TC/NVP regimen. Other ARV regimens were associated with a 1.80- to 3.19-fold increase in the risk of treatment discontinuation due to ADR ( P  < 0.0001 for all comparisons). ABC/3TC/NVP as a simplification regimen is a long-term effective regimen with lower discontinuation due to long-term toxicity compared with other standard ARV regimens.